2011
DOI: 10.1590/s0073-47212011000300001
|View full text |Cite
|
Sign up to set email alerts
|

Variação morfométrica em Bothropoides jararaca (Serpentes, Viperidae) no Rio Grande do Sul

Abstract: ABSTRACT. Morphometric variation in Bothropoides jararaca (Snakes, Viperidae) in Rio Grande do Sul. Although male and female snakes are born with the same size, growth rates and age of sexual maturation may be different, thus determining sexual dimorphism in the later stages of life. We evaluated the incidence of sexual and ontogenetic morphometric variation in Bothropoides jararaca (Wied, 1824), exploring relationships involving body size and sexual maturity through 14 morphometric variables. We analyzed 142 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
4
5
0
1
Order By: Relevance
“…We observed that the adult females of P. patagoniensis have a largest body size that than adult males (Table 1). A similar pattern of females were reported in several other species of snakes (Solorzano & Cerdas 1989, Shine 1993, Rivas & Burghardt 2001, Gregory 2004, Pinto & Fernandes 2004, Matias et al 2011, Mesquita et al 2011, Henao-Duque & Ceballos 2013.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We observed that the adult females of P. patagoniensis have a largest body size that than adult males (Table 1). A similar pattern of females were reported in several other species of snakes (Solorzano & Cerdas 1989, Shine 1993, Rivas & Burghardt 2001, Gregory 2004, Pinto & Fernandes 2004, Matias et al 2011, Mesquita et al 2011, Henao-Duque & Ceballos 2013.…”
Section: Discussionsupporting
confidence: 84%
“…Several authors observed that the fertility is considered one of the main selective agents for the larger size of females for some species of snakes; however, the largest size of males in another species of snakes can be considered as a significant feature of males of species that possesses the behaviour of competition for territory and for females in reproductive period (Shine 1978, 2000, Zug et al 2001, Matias et al 2011, Henao-Duque & Ceballos 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have discovered populations with larger body sizes or marked sexual dimorphism (e.g. Matias et al., 2011; Siqueira & Marques, 2018). Although studies addressing morphological divergences in snakes have been published extensively, many are focused only on one population, sympatric species or address only adults.…”
Section: Introductionmentioning
confidence: 99%
“…Machos de Bothrops jararaca de ambos os clados e das ilhas estudadas atingem a maturidade sexual com menor tamanho corporal do que as fêmeas, assim como observado em outras espécies do gênero Bothrops (VALDUJO et al, 2002;HARTMANN et al, 2004;MONTEIRO et al, 2006;NUNES et al, 2010;BARROS, 2011 HOGE et al, 1959;SOLÓRZANO;CERDAS, 1989;JANEIRO-CINQUINI et al, 1992;MANZANI, 1998;NOGUEIRA et al, 2003HARTMANN et al, 2004MONTEIRO et al, 2006;KASPEROVICZUS, 2009;NUNES et al, 2010;BARROS, 2011;MATIAS et al, 2011), mas também em outras espécies de serpentes PLUMMER, 1987;SCARTOZZONI, 2009;GOMES;. Essa característica ocorre provavelmente devido ao custo energético relacionado à fecundidade ser maior nas fêmeas (SHINE, 1978;BELL, 1980;FORD, 1987).…”
Section: Maturidade E Dimorfismo Sexual Intraespecíficounclassified